The cow tripped over the moon - Wilson, Tony, 1972-; Wood, Laura (Lindfield, NSW : Scholatic Press an imprint of Scholastic Australia Pty Limited, 2015)
Hey diddle diddle You all know the riddle A cow jumps over the moon... But the moon is very high in the sky. How many attempts will it take before Cow makes her famous high-flying leap?
For pre-school age.
Shortlisted for the Children's Book Council of Australia (CBCA) Award 2016, Early Childhood.
Keywords: Moon -- Pictorial works -- Juvenile fiction; Cows -- Juvenile fiction; Moon -- Juvenile fiction; Picture books; Children's stories; Fractured nursery rhyme; Nursery rhymes -- Juvenile fiction; Children's stories -- Pictorial works; Cows -- Pictorial works -- Juvenile fiction; Children's stories; Nursery rhymes; Moon -- Juvenile fiction; Australian; Picture books for children; Children's stories; Children's stories -- Pictorial works; Fiction; Juvenile works